Cardiac function after multimodal breast cancer therapy assessed with functional magnetic resonance imaging and echocardiography imaging - Heggemann, Felix; Grotz, Hanna; Welzel, Grit; Dösch, Christina; Hansmann, Jan; Kraus-Tiefenbacher, Uta; Attenberger, Ulrike; Schönberg, Stefan; Borggrefe, Martin; Wenz, Frederik; Papavassiliu, Theano; Lohr, Frank (International journal of radiation oncology, biology, physics, 2015)
Breast intensity modulated radiation therapy (IMRT) reduces high-dose heart volumes but increases low-dose volumes. We prospectively assessed heart changes after 3D conformal RT (3DCRT) and IMRT for left-sided breast cancer. Heart dose was analyzed individually, 3DCRT patients were moderately exposed, and IMRT was performed only in patients with unacceptably high heart doses upon 3DCRT planning. In 49 patients (38 patients received 3DCRT; 11 patients received IMRT; and 20 patients received neoadjuvant or adjuvant chemotherapy) magnetic resonance imaging (MRI) and echocardiography were performed before and at 6, 12, and 24 months after treatment. Mean heart dose for IMRT was 12.9 ± 3.9 Gy versus 4.5 ± 2.4 Gy for 3DCRT. Heart volumes receiving >40 Gy were 2.6% (3DCRT) versus 1.3% (IMRT); doses were >50 Gy only with 3DCRT. Temporary ejection fraction (EF) decrease was observed on MRI after 6 months (63%-59%, P=.005) resolving at 24 months. Only 3 patients had pronounced largely transient changes of EF and left ventricular enddiastolic diameter (LVEDD). Mitral (M) and tricuspid (T) annular plane systolic excursion (MAPSE and TAPSE) were reduced over the whole cohort (still within normal range). After 24 months left ventricular remodeling index decreased in patients receiving chemotherapy (0.80 vs 0.70, P=.028). Neither wall motion abnormalities nor late enhancements were found. On echocardiography, in addition to EF findings that were similar to those on MRI, global strain was unchanged over the whole cohort at 24 months after a transient decrease at 6 and 12 months. Longitudinal strain decreased in the whole cohort after 24 months in some segments, whereas it increased in others. Until 24 months after risk-adapted modern multimodal adjuvant therapy, only subclinical cardiac changes were observed in both 3DCRT patients with inclusion of small to moderate amounts of heart volume in RT tangents and in the patients treated with IMRT and reduced high-dose heart exposure.